Prediction of the Development of Persistent Massive Ascites After Living Donor Liver Transplantation Using a Perioperative Risk Score. Issue 6 (June 2018) - Wu, Yi-Ju; Wang, Shih-Ho; Elsarawy, Ahmed M.; Chan, Yi-Chia; Chen, Chao-Long; Cheng, Ben-Chung; Li, Lung-Chi; Chiu, Chien-Hua; Lee, Yi-Wei; Lin, Yu-Cheng; Wee, Sin-Yong; Pan, Cheng-Chung; et al.
Abstract : Background: Persistent massive ascites (PMAS) longer than 14 days after living donor liver transplantation is not uncommon and associated with worse outcome. A predictive risk scoring system was constructed after analysis of recipient, graft, and surgery-related factors. Methods: We retrospectively reviewed adult living donor liver transplantation recipients from 2005 to 2011 after excluding cases that experienced any intervention for perioperative vascular-related events. Two groups were identified, PMAS and non-PMAS. The score was constructed from significant factors using weighted odds ratios (OR). Results: The study population included 439 recipients. Persistent massive ascites was evident in 74 cases (17%). Five significant risk predictors were identified in multivariate analysis: pretransplant serum creatinine greater than 1.5 mg/dL (OR, 5.693; weighted OR, 2 ), recipient spleen to graft volume ratio greater than 1.3 (OR, 4.466; weighted OR, 2), left lobe graft (OR, 3.196; weighted OR, 1), more than 1000 mL ascites at laparotomy (OR, 2.541; weighted OR, 1), and graft recipient weight ratio less than 0.8 (OR, 2.419; weighted OR, 1). The clinical scoring system was constructed and ranged from 0 to 7. Receiver operating characteristic analysis showed an area under the curve (0.778, P < 0.001). Internal validation of the score showed an area under the curve of 0.783. The 5- and 10-year survival rates for the non-PMAS versus the PMAS groups were 89% and 84% versus 81% and 48%, respectively ( P = 0.001). Conclusions: The PMAS score is a predictive pretransplant clinical tool. A Clinical cutoff score of 4 might be decision-changing. Pretransplant correction of renal functions, deciding to harvest a large graft and/or consideration of splenic artery embolization could reduce the risk of PMAS. Abstract : The authors propose a predictive algorithm and a protective strategy to avoid prolong ascites after living donor liver transplantation.